Experimental identification of the mathematical model of the tram electric drive dynamic - Mokin, B. I.; Mokin, O. B. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Methods for the experimental determination of the parameters of the mathematical model of the dynamic of the tram electric drive are developed. The suggested methods account both the peculiarities of the tram, connected with its simultaneous movement in time and space, and the fact that the electric motors of its electric drive are conected to contact system in pairs and have series.